Considerații teoretice privind guvernarea, regimul politic și regimul de guvernare [Articol] - Cârnaț, Teodor; Popa, Cristina (My University, 2017)
This article deals with definition and analysis of the core concepts of a democratic regime. These concepts are: governance, regime, parliamentarism, presidentialism, state power separation, governing regime and its consolidation. The concept of governing regime is a new one and starts from a classification of political regime. This classification is ambiguous and many scholars make confusions between the concepts. That is why this article comes into explaining this notion by simplifying and excluding the confusions in this domain. The article ends with personal definition of the governing regime that is a system of organization and exertion of state power through which is realized the distribution of power between different categories of bodies and that ensures the independence, collaboration and reciprocal control of political institutions.
Keywords: regime; governance; governing regime; democracy; rule of law; political regime